2010
DOI: 10.1016/j.neurobiolaging.2008.09.005
|View full text |Cite
|
Sign up to set email alerts
|

ApoE genotype and abnormal auditory cortical potentials in healthy older females

Abstract: Apolipoprotein E (ApoE) status and gender are risk factors for the development of Alzheimer's disease. Alzheimer's disease is more prevalent in female relative to male carriers of the ApoE 4 gene. We examined cortical sensory (P50, N100) and cognitive (P300) potentials in an auditory target detection task in females as a function of ApoE genotype (ApoE 4 carriers, ApoE 4 non-carriers) to define the incidence of abnormalities prior to the clinical expression of cognitive impairments. Both neuropsychological tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…In addition, during the visible learning trials of Memory Island, there was a genotype × sex interaction. With the heightened sensitivities of females to the consequences of apoE4 (11,38), these findings highlight the importance for future investigations to carefully monitor for apoE by sex interactions or to continue examining females separately (37,39). Sex differences, independent of apoE4, were also identified in the spatial learning trials of Memory Island with boys showing greater velocity and reaching the target sooner than girls, consistent with faster and more accurate performance by males than females in virtual water mazes across the lifespan (13,33,40,41).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, during the visible learning trials of Memory Island, there was a genotype × sex interaction. With the heightened sensitivities of females to the consequences of apoE4 (11,38), these findings highlight the importance for future investigations to carefully monitor for apoE by sex interactions or to continue examining females separately (37,39). Sex differences, independent of apoE4, were also identified in the spatial learning trials of Memory Island with boys showing greater velocity and reaching the target sooner than girls, consistent with faster and more accurate performance by males than females in virtual water mazes across the lifespan (13,33,40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Methodological differences complicate comparison across studies; however, studies that failed to show significantly larger P50 amplitudes in AD patients relative to those from age-matched controls have included a more severe cohort in the mild-to-moderate AD range (e.g., MMSE = 13.2±5.4) (Golob et al, 2007) than in the very mild range (e.g, MMSE = 23 ± .9)(Cheng et al, 2012; Golob and Starr, 2000). In contrast, P50 latency has been comparable between clinical groups and age-matched controls (Cheng et al, 2012; Golob and Starr, 2000; Golob et al, 2007; Irimajiri et al, 2005; Irimajiri et al, 2010) in all but one study that found longer latencies in MCI patients and a correlation between larger amplitude and longer latency P50 response to distractor tones (Golob et al, 2002). …”
Section: Introductionmentioning
confidence: 90%
“…The later component P3 has been shown to be associated with APOE in healthy controls. Irimajiri et al [81] found reduced amplitude among healthy female e4 carriers in auditory task, and Espeseth et al [82] found e4-related reduction of visual P3a amplitudes. Together, these findings indicate a potential clinical significance of individual differences in the attention-related ERP components N1, N2, and P3.…”
Section: Nonmemory Findings Associated With Genetic Risk Of Admentioning
confidence: 99%